Analisis Risk Tolerance dan Overconfidence terhadap Keputusan Investasi di Bursa Efek Indonesia - Widiastuti, Widiastuti; Soleha, Erin; Meirani, Nadia (Universitas Hamzanwadi, 2024)
In Indonesia, investment is now commonplace for Indonesian people, plus the increasingly rapid development of technology and digitalization, makes it easier for people to invest. We cannot necessarily invest for the reason of keeping up with the times, if this is not taken into consideration when making investment decisions it could be detrimental, while the aim of investment is for profit. When making investment decisions, we must consider how investors have risk tolerance and overconfidence. The aim of this research is so that the decisions we take in determining investment success on the Stock Exchange can be carried out optimally. The main data used in this research comes from interviews and data collection methods for 100 respondents using Accidental Sampling in the millennial population of the Bekasi area. The study methodology takes a quantitative tack. Using SmartPLS software, the Partial Least Square statistical test tool was used to evaluate the indicators for each variable. According to the study's findings, overconfidence affects investment decisions made on the Indonesian Stock Exchange, while risk tolerance has no bearing on such decisions